Takayasu’s Arteritis - Angelina Febrina (Cermin Dunia Kedokteran, 2015)
Takayasu’s arteritis (TA) is a chronic inflammatory arteritis that commonly affects aorta and its branches. The exact etiology of TA remains unknown, but many researchers believed that it is autoimmune in nature. Eventhough TA is categorized as a rare disease, the prevalence rate is 2.6 per million annually, and its complications can be life-threatening. Early diagnosis and treatment may prevent the irreversible damage in the affected vessels and improve treatment outcome. This review article provides a brief summary of etiopathogenesis, clinical diagnosis, and treatment options for TA.Takayasu’s arteritis (TA) adalah suatu penyakit inflamasi arteri kronik yang biasanya mempengaruhi aorta dan cabang-cabangnya. Penyebab pasti penyakit ini belum diketahui, tetapi banyak peneliti percaya bahwa TA merupakan suatu penyakit autoimun. Walaupun TA merupakan kategori penyakit yang jarang - prevalensinya 2.6 kasus per juta orang setiap tahun, dan komplikasi TA dapat sangat membahayakan. Diagnosis dan pengobatan awal dapat mencegah kerusakan permanen pembuluh darah yang terkena dan dapat memperbaiki hasil pengobatan. Tinjauan pustaka ini membahas secara singkat etiopatogenesis, diagnosis klinis, dan pengobatan penyakit TA.